Investigation of Sick Building Syndrome (SBS) Through Student Perceptions of the Indoor Environmental Quality (IEQ) of School Building Near the Airport - Gamalia, Auditha Nurul; Ekasiwi, Sri Nastiti N.; Samodra, FX Teddy Badai; Fitriaty, Puteri; Mustakima, Dui Buana (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2025)
School buildings that use natural ventilation have challenges to Sick Building Syndrome (SBS) due to high noise intensity and the need to circulate air by opening windows. This study investigated SBS symptoms in schools closest to the airplane runway. Subjective measurements were carried out using self-administrative questionnaires to determine students’ perceptions. Objective measurements to obtain Indoor Environmental Quality (IEQ) data were carried out through an experiment of opening a window with an awning window type as far as 11 cm or 1/2 of the window span with an angle of 12.5. The average results of IEQ measurements on the thermal aspect include a temperature of 30.1 C, CO2 levels of 331 ppm, and wind speeds of 0.1-0.3 m/s have met the minimum comfort standards. However, the average humidity in the classroom has not been met. In addition, classroom noise is still far from the comfort standard, which is 70-109 dB. However, the results of the evaluation of students’ perception assessments of the IEQ of the room showed no symptoms of SBS in terms of physical and psychological aspects. Most students were not disturbed by the less-than-ideal thermal and acoustic conditions. However, students can experience long-term health problems and potentially experience psychological stress if they are continuously exposed to high levels of noise and less-than-ideal IEQ conditions.